Staatsauflösung und Kriegsfinanzen: Zur Rolle der Kriminalität im Kosovo Konflikt - Andrees, Beate (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
The article explains criminal dimensions of ethnic conflicts through the interconnection of transnational diaspora communities and mafia networks with local “warlord regimes”. It is argued that by supporting local warlords, which have partly or in total replaced state institutions, these networks contribute to the intensification and prolongation of the conflict. Moreoever, they are democratically not legitimated and provide security as well as access to resources on highly exclusive terms. The case of Kosovo demonstrates that intervention is unlikely to break these long established informal structures, especially if international institutions such as the UN are not accepted by the local population.